Initial Evaluation of an Adenosine A 2A Receptor Ligand, 11 C-Preladenant, in Healthy Human Subjects - Sakata, Muneyuki; Ishibashi, Kenji; Imai, Masamichi; Wagatsuma, Kei; Ishii, Kenji; Zhou, Xiaoyun; de Vries, Erik F.J.; Elsinga, Philip H.; Ishiwata, Kiichi; Toyohara, Jun (Journal of Nuclear Medicine, 2017)
C-preladenant is a selective antagonist for mapping of cerebral adenosine A receptors (A Rs) by PET. This is a first-in-human study to examine the safety, radiation dosimetry, and brain imaging of C-preladenant in healthy human subjects. Dynamic C-preladenant PET scans (90 min) were obtained in 5 healthy male subjects. During the scan, arterial blood was sampled at various time intervals, and the fraction of the parent compound in plasma was determined. For anatomic coregistration, T1-weighted MRI was performed. The total distribution volume ( ) was estimated using 1- and 2-tissue-compartment models (1T and 2T, respectively). The distribution volume ratio (DVR) was calculated from of target and reference region and obtained with a noninvasive Logan graphical reference tissue method ( * = 30 min). The applicability of a shortened protocol as an alternative to the 90-min PET scan was investigated. Tracer biodistribution and dosimetry were determined in 3 healthy male subjects, using serial whole-body PET scans acquired over 2 h after C-preladenant injection. There were no serious adverse events in any of the subjects throughout the study period. C-preladenat readily entered the brain, with a peak uptake in the putamen and head of the caudate nucleus 30-40 min after tracer injection. Other brain regions showed rapid clearance of radioactivity. The regional distribution of C-preladenant was consistent with known A R densities in the brain. At pseudoequilibrium (reached at 40 min after injection), stable target-to-cerebellar cortex ratios of around 3.8-10.0 were obtained. The 2T fit better than the 1T in the low-density A R regions. In contrast, there were no significant differences between 1T and 2T in the high-A R-density regions. DVRs in the putamen and head of the caudate nucleus were around 3.8-10.3 when estimated using a Logan graphical reference tissue method with cerebellum as the reference region. PET scanning at 50 or 70 min can provide the stable DVR estimates within 10% or 5% differences at most, respectively. The radioactivity was mainly excreted through the hepatobiliary system after C-preladenant injection. As a result, the absorbed dose (μGy/MBq) was highest in the gallbladder wall (mean ± SD, 17.0 ± 2.5) and liver (11.7 ± 2.1). The estimated effective dose for C-preladenant was 3.7 ± 0.4 μSv/MBq. This initial evaluation indicated that C-preladenat is suitable for imaging of A Rs in the brain.